THE INFLUENCE OF DISCIPLINE, COMPETENCE, ORGANIZATIONAL CULTURE AND QUALITY OF LEADERSHIP ON TEACHER PERFORMANCE IN SMK BATIK 2 SURAKARTA - Purnanto Purnanto; Bambang Mursito; Istiatin Istiatin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Teacher discipline and organizational culture practices in schools and teacher competence and leadership of school principals greatly affect teacher performance at SMK Batik 2 Surakarta. This study aims to determine whether discipline, competence, organizational culture and leadership quality have a simuly effect on teacher performance at SMK Batik 2 Surakarta. This type of research is a type of quantitative research, conducted at SMK Batik 2 Surakarta. The research time was carried out for one month, namely in December 2020. The research population was 50 people using a non-probability sampling technique with the technique taken, namely saturated sampling (census) with a sample of 50 people. Data collection is done by observing, documenting and asking questions. The data analysis technique was carried out with the classical assumption test, namely normality test, multicollinearity test, as well as heteroscedasticity test and multiple regression analysis as well as model suitability test (Good of Fit) by analyzing the coefficient of determination (R2), F test, t test and the coefficient of determination ( R2). The results showed that: 1) there was a positive and significant influence on teacher perceptions of discipline on the teacher's performance at SMK Batik 2 Surakarta supported by empirical evidence, 2) there was a positive and significant influence on organizational culture on teacher performance at SMK Batik 2 Surakarta supported by empirical evidence, 3 ) there is a positive and significant effect of teacher competence on teacher performance at SMK Batik 2 Surakarta supported by empirical evidence, 4) there is a positive and significant influence on leadership quality on teacher performance at SMK Batik 2 Surakarta supported by empirical evidence. Keywords: Discipline, organizational culture, teacher competence, leadership quality.